2015
DOI: 10.1007/s13753-015-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost Thaw and Associated Settlement Hazard Onset Timing over the Qinghai-Tibet Engineering Corridor

Abstract: In permafrost areas, the timing of thermal surface settlement hazard onset is of great importance for the construction and maintenance of engineering facilities. Future permafrost thaw and the associated thermal settlement hazard onset timing in the Qinghai-Tibet engineering corridor (QTEC) were analyzed using high-resolution soil temperature data from the Community Land Model version 4 in combination with multiple model and scenario soil temperature data from the fifth phase of the Coupled Model Intercomparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 40 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…It is therefore extremely vulnerable to climate change (Cheng, 1999). Permafrost degradation not only strongly affects local hydrological processes, soil biogeochemical cycles and regional atmospheric circulation but also intensifies climate warming and exerts great impacts on human activity (Nelson et al, 2001;Nelson, 2003;Guo et al, 2012;Guo and Sun, 2015;Guo and Wang, 2017). Several studies have reported extensive shrinkage of permafrost on the TP under climate warming (Wang, 1997;Cheng and Wu, 2007;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore extremely vulnerable to climate change (Cheng, 1999). Permafrost degradation not only strongly affects local hydrological processes, soil biogeochemical cycles and regional atmospheric circulation but also intensifies climate warming and exerts great impacts on human activity (Nelson et al, 2001;Nelson, 2003;Guo et al, 2012;Guo and Sun, 2015;Guo and Wang, 2017). Several studies have reported extensive shrinkage of permafrost on the TP under climate warming (Wang, 1997;Cheng and Wu, 2007;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The thawing of permafrost can result in the release of soil organic carbon, the melting of ground ice, and changes in the seasonal soil freezing and thawing processes. These changes will, in turn, affect the climate (Li & Chen, ; Schuur et al, ), the hydrology and availability of water resources (Guo, Wang, & Li, ; Liljedahl et al, ), the stabilization of engineering facilities underlain by permafrost (Guo & Sun, ; Guo & Wang, ; Nelson et al, ), and the terrestrial ecosystem (Qin, Zhou, & Xiao, ; Yang et al, ). Therefore permafrost has an important role in the climate system of a warming world.…”
Section: Introductionmentioning
confidence: 99%
“…Ground instability is impacting the dense network of equipment and infrastructures existing in these regions [22,41,42]. With the warming climate anticipated during the next decades, it is expected that permafrost degradation will increase in these regions and therefore local, regional and national administrations will have to invest large sums to adapt the infrastructures to the changing landscape [37,42,43].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%